Estudo do agregado graúdo reciclado de concreto como agente de cura interna em concreto com cinza de casa de arroz - Jordani, Bárbara (Universidade do Vale do Rio dos Sinos, 2016)
During the last years, the construction sector has been looking for alternatives to replace the raw materials used for concrete production, in order to reduce environmenal impact. The waste recycling as raw material for civil construction can be one of solutions to this problem. One example of this kind of solution is to use the recycled concrete aggregate, which can be used as alternative for the natural aggregate. Another possibility is to use some waste as pozzolanic material, as the rice husk ash. After the burning of the rice hull, it becomes the ash, which has a large concentration of silica. The use of these pozzolans can contribute to reduce the consumption of cement. Furthermore, the usage of pre-saturated recycled aggregate can act as an internal concrete curing agent, which in the case of concretes with pozzolans can be a good way to obtain a better hydration of the binder paste. This study proposes to investigate the effect of the usage of concrete recycled coarse aggregate (RCCA) as an internal curing agent in concrete produced with pozzolan, in order to evaluate the durability and mechanical behaviour. It was evaluated the replacement of natural coarse aggregate (AN) by RCCA. The content of RCCA is related to the binder consumption and it was employed dry and wet. The cement replacement by rice husk ash was done at 20% and it was used three water to binder (w/t) relationships (0.31, 0.42, and 0.53). The curing process was developed in two cure environments (U.R 60% and 100%).The results indicated that the CCA produces positive effect on concrete made with AGRC. The concrete made with respect to w/b 0.31 for all tested concretes returned resistances in the range of 35-45 MPa. The effect of RCCA as internal curing agent is significant when the concrete is cured in a humid environment only for compressive strength. In dry environment, it does not work as internal curing agent. It was also noted significant retractions up to 28 days. As for domestic demand it is noteworthy that the saturated employee AGRC has no internal curing agent behaviour, especially in the critical environment with relative humidity of around 60%, considered low.
Keywords: Agregado reciclado de concreto; Cura interna; Retração; Cinza de casca de arroz; Recycled aggregate concrete; Internal curing; Retraction; Rice husk ash; ACCNPQ::Engenharias::Engenharia Civil